A pedagogia no capsi: construindo práticas de cuidado e aprendizagem - Cunha, Luisa Maria Nunes da (Universidade Federal Rural do Semi-Árido, 2019)
A CAPSi pedagogy, building care and learning practices, is a study that analyzes how a CAPS pedagogue updates her care and learning practices through an experience of self-narrative composition about the process itself. A motivation for the construction of the research was given to the author's inquiries related to work with children and adolescents involved with mental disorders / psychological distress. As the goal of the search to understand how the pedagogy present in a mental health environment can favor the construction of methods to improve the quality of life of the subjects attended. The theoretical study for analysis is built on existing studies of psychology in psychosocial care centers, a first-person methodology, and a perspective on enaction and autopoiesis as tools for thinking about how we will improve the experience yourself. The writing presents the support of theoretical networks as the foundation of the experience of pedagogy in mental health, encompassing the history of mental health; Caps implantation tracking in Brazil, Rio Grande do Norte and Mossoró-RN, as well as interaction with papers that discuss CAPS pedagogy. How the learning and research contributions, including the Child and Adolescent Psychosocial Care Center (CAPSi), are tracking the reconstruction of pedagogy, their experience, and interacting with different professionals who study children or adolescents with autism, depression or disability. Intellectual, moderate, severe, cerebral palsy, schizophrenia, among others. Therapeutic spaces become more potent when they are lived together, where the individual also participates in the process, interacting with a multiprofessional team and other users. Even the same position you feel when taking a medicine, realize that is more cheerful, quiet, or more agitated, sad, confident. Dedicate to talk about how an experience happens as an important strategy for pedagogy work with the team. The pedagogue offers the group the possibility of work to reconstruct the notions of learning, considering to be in the context of mental health; to rethink about the affection so present in the pedagogical discourse, what in mental health we start thinking about how we deal with the catalytic affect and, in our experience, the pedagogue can favor the attention networks, the experience of children. and adolescents in the context of inclusive education and mental health, helping to make networks effectively exist. We understand that through interaction involving processes of connection with oneself and living with one another, we can learn as a pedagogue to deal with differences in our own lives and thus give ourselves and others opportunities to learn and practice. care needed to improve human life.
Keywords: Pedagogia; Saúde Mental; Práticas de cuidado; Aprendizagem; Autonarrativas; Pedagogy; Mental health; Care practices; Learning; Autonarratives; MULTIDISCIPLINAR::INTERDISCIPLINAR::COGNIÇÃO, TECNOLOGIAS E INSTITUIÇÕES